Clinical pharmacokinetics of oral drugs in the treatment of multiple myeloma. Issue 3 (27th November 2017) - Morival, Camille; Oumari, Sitty; Lenglet, Arthur; Le Corre, Pascal
Abstract: Treatment of myeloma is a long‐term treatment mainly based on all‐oral combinations of drugs. Because oral drugs have a more complex pharmacokinetics compared with IV treatments, an appropriate knowledge of the factors that may alter their systemic exposure is of particular clinical relevance. Both drug‐drug interactions, food‐effect, and dose‐adaptation in renal and hepatic impairment may influence the systemic drug levels with a potential impact on drug efficacy or safety. Moreover, a better control of drug exposure may improve the side effect profiles of these treatments with a favourable impact on patient compliance. Furthermore, as long‐term treatments, these drugs may also alter the systemic exposure of coadministered medications in these rather old patients. The aim of this review was to identify the factors modifying the systemic exposure of oral drugs used in myeloma by focusing on the pharmacokinetic drug‐drug interactions and the effects of renal and hepatic impairment and of food impact.